Excited-state intramolecular proton transfer reactions of 2,5-bis(2′-benzoxazolyl)hydroquinone and its water cluster exhibiting single and double proton transfer: A TD-DFT dynamics simulation - Rathawat Daengngern (2019)
© 2019 Elsevier B.V. Detailed pictures of the excited-state intramolecular proton transfer (ESIPT)of 2,5-bis(2′-benzoxazolyl)hydroquinone (BHQ)and its water cluster have been investigated by dynamics simulations on the first lowest-excited energy using time-dependent density functional theory (TD-DFT). We focused on the structural, photophysical and dynamic properties of BHQ in the absence and presence of water molecules through intermolecular hydrogen bonds (interHBs). Our dynamics simulations reveal three possible mechanisms of the ESIPT processes: i)no proton transfer (No PT); ii)single PT (SPT); and iii)double PT (DPT), that could take place within the PT time of 160 fs via intrinsic intramolecular hydrogen bonds (intraHBs). The ESIPT mechanism of isolated BHQ elucidates that back PT is likely to be found at 64% rather than the SPT (32%)and DPT (4%), which is in good agreement with the experiments of dual fluorescence from di-enol and mono-keto emissions. Notably, the results from BHQ with water (BHQ-(H2O)2)reveal that the participation of water might produce a remarkable effect on promoting the SPT process up to 60% and DPT up to 7 times when compared to conditions of no water. The simulated probability of PT is well related to possible PT mechanisms regarding different tautomers in the fluorescence spectra found in previous experiments. The existence of di-keto tautomer arose from the DPT of BHQ and its water cluster and was not observed in the UV/Vis spectrum.